Dynamics of the metal binding domains and regulation of the human copper transporters ATP7B and ATP7A. Issue 4 (8th March 2017) - Yu, Corey H.; Dolgova, Natalia V.; Dmitriev, Oleg Y.
Abstract: Copper transporters ATP7A and ATP7B regulate copper levels in the human cells and deliver copper to the biosynthetic pathways. ATP7A and ATP7B belong to the P‐type ATPases and share much of the domain architecture and the mechanism of ATP hydrolysis with the other, well‐studied, enzymes of this type. A unique structural feature of the copper ATPases is the chain of six cytosolic metal‐binding domains (MBDs), which are believed to be involved in copper‐dependent regulation of the activity and intracellular localization of these enzymes. Although the structures of all the MBDs have been solved, the mechanism of copper‐dependent regulation of ATP7B and ATP7A, the roles of individual MBDs, and the relationship between the regulatory and catalytic copper binding are still unknown. We describe the structure and dynamics of the MBDs, review the current knowledge about their functional roles and propose a mechanism of regulation of ATP7B by copper‐dependent changes in the dynamics and conformation of the MBD chain. Transient interactions between the MBDs, rather than transitions between distinct static conformations are likely to form the structural basis of regulation of the ATP‐dependent copper transporters in human cells. © 2016 IUBMB Life, 69(4):226–235, 2017